2006
DOI: 10.1124/mol.106.027896
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Responsiveness to Ezetimibe Correlates with Niemann-Pick C1 Like-1 (NPC1L1) Binding Affinity: Comparison of Multiple Species NPC1L1 Orthologs

Abstract: Ezetimibe is the first in class 2-azetidinone that decreases plasma cholesterol by blocking intestinal cholesterol absorption. Ezetimibe effectively reduces plasma cholesterol in several species including human, monkey, dog, hamster, rat, and mouse, but the potency ranges widely. One potential factor responsible for this variation in responsiveness is diversity in ezetimibe metabolism. After oral administration, ezetimibe is glucuronidated. Both ezetimibe and the glucuronide lower plasma cholesterol; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 36 publications
4
47
0
1
Order By: Relevance
“…It has been shown that both ezetimibe and its glucuronide metabolite inhibit cholesterol absorption but that the glucuronide derivative is more potent. This is likely related to the enhanced binding affinity of the glucuronide metabolite to NPC1L1 (4,8,(27)(28)(29). Thus, our observations with the parent drug may underestimate the effects of the glucuronyl metabolite.…”
Section: Discussionmentioning
confidence: 89%
“…It has been shown that both ezetimibe and its glucuronide metabolite inhibit cholesterol absorption but that the glucuronide derivative is more potent. This is likely related to the enhanced binding affinity of the glucuronide metabolite to NPC1L1 (4,8,(27)(28)(29). Thus, our observations with the parent drug may underestimate the effects of the glucuronyl metabolite.…”
Section: Discussionmentioning
confidence: 89%
“…Atorvastatin inhibits hepatic cholesterol synthesis by inhibiting HMG-CoA reductase, whereas ezetimibe inhibits the intestinal absorption of cholesterol by binding Niemann-Pick C1 like-1 ( 33 ). In addition, because Niemann-Pick C1 like-1 is expressed in hepatocytes and biliary epithelial cells as well as in enterocytes ( 34 ), ezetimibe may interrupt the hepatic recycling of cholesterol secreted into bile and taken up by biliary duct epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were extended to include binding to mouse, hamster, rabbit, and canine NPC1L1, which correlated to the in vivo activity of ezetimibe 20) . Binding studies with multiple species NPC1L1 orthologs also demonstrated that the binding affinity for the glucuronide metabolite was 2-10 fold higher than ezetimibe.…”
Section: Discovery Of the Molecular Target Of Zetiamentioning
confidence: 99%